Microneurovascular reimplantation in a case of total penile amputation - Bhatt Yogesh; Vyas Kinnari; Srivastava Rajat; Panse Nikhil (Indian Journal of Plastic Surgery)
Amputation of the penis is a rare condition reported from various parts of the world as isolated cases or small series of patients; the common aetiology is self-mutilating sharp amputation or an avulsion or crush injury in an industrial accident. A complete reconstruction of all penile structures should be attempted in one stage which provides the best chance for full rehabilitation of the patient. We report here a single case of total amputation of the penis, which was successfully reattached by using a microsurgical technique. After surgery, near-normal appearance and function including a good urine flow and absence of urethral stricture, capabilities of erection and near normal sensitivity were observed.